Digital capital and digital inequalities among students - Čikić, Jovana M; Kišjuhas, Aleksej (Sociološki pregled, 2024)
The aim of the paper is to analyze the characteristics of students` digital capital, with a particular focus on education and digital inequalities. It is assumed that students` digital capital is relatively high, as they are digital natives. Auxiliary hypotheses relate to characteristics of digital capital in education, as well as the dependence of digital capital on students` socio-demographic and educational characteristics. The analysis is based on the data from a survey conducted on a sample of 438 students. For the purposes of the analysis, a five-dimensional index of students` digital capital was constructed. The results partially confirm the main hypothesis and an auxiliary one, while the hypotheses regarding digital capital in education and the impact of educational portfolio are fully confirmed.
Keywords: higher education; digital capital; digital inequalities; index of students` digital capital; students